Outbreak of Adenovirus serotype 8 keratoconjunctivitis in Puducherry, South India: a molecular epidemiological study - Raja Sundaramoorthy; Rahul Dhodapkar; Subashini Kaliaperumal; Belegode Narasimha Harish (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links below to access the Full Text.